Regioselective Synthesis of 5-(Trifluoromethyl)[1,2,4]triazolo[1,5-a]pyrimidines from β-Enamino Diketones - Andrade, Valquiria P.; Mittersteiner, Mateus; Bonacorso, Helio G.; Frizzo, Clarissa P.; Martins, Marcos A. P.; Zanatta, Nilo (Synthesis, 2019)
The use of β-enamino diketones as an easy entry to the regioselective synthesis of [1,2,4]triazolo[1,5-a]pyrimidines is reported. These ketones reacted with 3-amino-1H-1,2,4-triazoles to furnish exclusively 6-substituted 5-(trifluoromethyl)[1,2,4]triazolo[1,5-a]pyrimidines in yields of up to 95%. The regioselectivity of the reactions performed was maintained regardless of the substituent in the starting ketone or aminoazole.
Keywords: β-enamino diketones; 1,3-diones; triazolopyrimidines; aminotriazoles; fluorinated heterocycles